(untitled) (CIPEEX, 2025)
Disinformation and fake news are false or manipulated information that circulates primarily on the internet and social media, with the aim of deceiving, confusing, or influencing public opinion. This unreliable information poses a major challenge to democracy, as it compromises citizens’ right to access truthful and reliable information, which is essential for forming informed opinions and ensuring a free vote. During election periods, the spread of fake news increases considerably, being used to attack candidates, spread rumors, or manipulate results. This results in political disagreement, a decline in the value of organizations, and distrust in the electoral system. In this regard, it is important to note that when disinformation is used in an organized manner or even manipulated to influence elections, it can be considered an electoral crime (Law No. 9,504/1997). In Brazil, the Electoral Court works to combat crimes, which include the dissemination of knowingly false information about parties or candidates, misuse of social media, and illegal content promotion. Furthermore, digital education and fact-checking campaigns help mitigate the impact of fake news. It is important to emphasize that combating disinformation requires collaboration between the government, technology companies, the press, and civil society. It is essential to promote media literacy, encourage critical thinking, and hold accountable those who produce and disseminate false content, thus ensuring the integrity of the democratic process.